Dose-staged Gamma Knife radiosurgery for meningiomas: A retrospective study in a single center - Gong, Xiu; Ding, Jianbo; Knisely, Jonathan P. S.; Wang, Enmin; Pan, Li; Wang, Binjiang; Zhang, Nan; Wu, Hanfeng; Dai, Jiazhong; Yu, Tonggang; Tang, Xuqun (Frontiers in Neurology, 2022)
Objective This study aimed to study the efficiency and safety of a dose-staged Gamma Knife radiosurgery strategy for large meningiomas or meningiomas close to important nerve structures. Methods This study evaluates the outcome of a prospectively accrued series of 71 consecutive patients with meningiomas treated with staged dose-fractionated Gamma Knife radiosurgery. The average peripheral doses for the first and second fractions were 9.0 ± 0.9 Gy (8–12 Gy) and 8.6 ± 0.7 Gy (range, 7–10 Gy), respectively. The interval between fractions was 6.1 ± 1.9 months (range, 3–12 months). The median follow-up time was 36 months (12–96 months). Results During the follow-up period after the second fraction, 97.2% achieved tumor control in our series. A total of 2 patients exhibited local recurrence at 30 and 60 months after the second fraction, respectively. No treatment-related complications or new long-term neurological dysfunctions were reported. MRIs observed slightly or moderately increased peritumoral edema in six patients, but no specific neurological complaints are attributed to this finding. Conclusion This study investigates the efficiency and safety of dose-staged Gamma Knife radiosurgery as an alternative option for meningiomas that were large in volume, adjacent to crucial structures, or in patients with contraindications to craniotomy.